2016
DOI: 10.4238/gmr.15017254
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic changes in maize as a response to heavy metal (lead) stress revealed by iTRAQ quantitative proteomics

Abstract: ABSTRACT. Lead (Pb), a heavy metal, has become a crucial pollutant in soil and water, causing not only permanent and irreversible health problems, but also substantial reduction in crop yields. In this study, we conducted proteome analysis of the roots of the non-hyperaccumulator inbred maize line 9782 at four developmental stages (0, 12, 24, and 48 h) under Pb pollution using isobaric tags for relative and absolute quantification technology. A total of 252, 72 and 116 proteins were differentially expressed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Thus, YE8112 had a more limited proteome response. A series of reports on maize seedling-stage abiotic stress analyses between different inbred lines exist [ 2 , 4 ]. In particular, Li et al [ 2 ] found relatively large number of differentially expressed genes (DEGs) in freezing-sensitive inbred line Hei8834 than freezing-tolerant line KR701 after freezing treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, YE8112 had a more limited proteome response. A series of reports on maize seedling-stage abiotic stress analyses between different inbred lines exist [ 2 , 4 ]. In particular, Li et al [ 2 ] found relatively large number of differentially expressed genes (DEGs) in freezing-sensitive inbred line Hei8834 than freezing-tolerant line KR701 after freezing treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A series of reports on maize seedling-stage abiotic stress analyses between different inbred lines exist [ 2 , 4 ]. In particular, Li et al [ 2 ] found relatively large number of differentially expressed genes (DEGs) in freezing-sensitive inbred line Hei8834 than freezing-tolerant line KR701 after freezing treatment. Similarly, Zheng et al [ 4 ] realized greater proportion of DEGs in drought-sensitive Ye478 than drought-tolerant Han21 after drought treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, a customized ratio was calculated for every protein group as the median of all PSMs included in the protein group. Only ratios with P < 0.05 and only fold-changes ≥ 2.0 across two aliquot replicates were used to determine up- or down-regulated proteins [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that iTRAQ is an effective method for examining proteins that are differentially expressed under different stressful physiological conditions. For example, it has been used in a proteomic analysis of grapevine leaves under heat stress conditions , and to investigate the response of maize to heavy metal (lead) stress (Li et al, 2016). To the best of our knowledge, only a few proteomic studies have been conducted on low potassium levels in plants, and these have been on Arabidopsis (Kang et al, 2004) and ramie (Deng et al, 2014).…”
Section: Introductionmentioning
confidence: 99%